Kajian Daya Dukung Jalan dan Prioritas Penanganannya di Perbatasan Kota Depok dengan Kota Administrasi Jakarta Selatan - Corry Nurmala; Baba Barus; Umar Mansyur (TATALOKA, 2020)
Roads carrying capacity can be interpreted as a road capacity to support passing vehicles. This study was aimed to determine the priority of road handling at border of Depok City with South Jakarta by looking at the physical condition, road equipment and supporting facilities, costumer satisfaction and roads carrying capacity. Using descriptive analysis method for the physical conditions of roads and road equipment, CSI methods for the results of questionnaires and LoS for roads carrying capacity. The results showed that the road conditions in the category of moderate and lightly damaged conditions, conditions of road equipment and supporting facilities in South Jakarta were better than those on roads in Depok City and roads costumer satisfaction index in the category was less satisfied and quite satisfied. Roads carrying capacity at the border is in the fairly good to very bad category. The priority of road handling is determined, for roads at  Depok City are first priority for Margonda Road, second priority for Kukusan Raya Road and Tanah Baru Road and for roads at South Jakarta are first priority for Lenteng Agung Raya Road, second priority for Srengseng Sawah Road, third priority for Moh. Kahfi 1 Road and Moh. Kahfi 2 Road.Keywords: Carrying Capacity, Handling Priority, Road